2005
DOI: 10.1002/mrm.20348
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between magnetization transfer and blood‐oxygen‐level‐dependent effects

Abstract: Low-power off-resonance spin-echo magnetization transfer (MT) imaging experiments with a long repetition time (TR) were performed on rat brain for a range of arterial PCO 2 levels. The measured magnetization transfer ratio decreased with increased arterial PCO 2 levels. When performing blood-oxygenlevel-dependent (BOLD) functional magnetic resonance imaging (fMRI)-type data analysis in which signal intensities were normalized to the normocapnic state, the CO 2 -based BOLD effect was much stronger with than wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Their method can be used at high field MRI, where venous blood is invisible due to short T2*. When removing tissue signal (as much as up to 60%) using magnetization transfer (MT) weighting, CBV a can be derived using the knowledge that blood is not affected when irradiating sufficiently off-resonance (Hua et al, 2009; Wolff and Balaban, 1989; Zhou et al, 2005). They did not separate out capillary effects, but mention that part of the early capillaries are included in their CBV a .…”
Section: Compartmentation Of Bold and Vascular Effectsmentioning
confidence: 99%
“…Their method can be used at high field MRI, where venous blood is invisible due to short T2*. When removing tissue signal (as much as up to 60%) using magnetization transfer (MT) weighting, CBV a can be derived using the knowledge that blood is not affected when irradiating sufficiently off-resonance (Hua et al, 2009; Wolff and Balaban, 1989; Zhou et al, 2005). They did not separate out capillary effects, but mention that part of the early capillaries are included in their CBV a .…”
Section: Compartmentation Of Bold and Vascular Effectsmentioning
confidence: 99%
“…Initially, human neural activation studies found that MT reduced the BOLD percentage signal change for most activated pixels, and that MTR increased with task activation (5). In contrast, recent hypercapnia studies in rat found that MT increased the BOLD percentage signal change, and that MTR decreased with arterial partial pressure of CO 2 (PACO 2 ) levels (6). Further studies are necessary to understand BOLD signals with MT effects.…”
mentioning
confidence: 92%
“…Signal intensity measurements with vs. without off‐resonance irradiation give the MT attenuation factor (1 – MTR), where MTR is the MT ratio, which accounts for both MT (spin exchange and cross relaxation) and any potential direct saturation effects of the off‐resonance pulse (3). Functional blood‐oxygenation‐level–dependent (BOLD) studies incorporating off‐resonance spin preparation have examined the effects on functional MRI (fMRI) contrast (4–6). Initially, human neural activation studies found that MT reduced the BOLD percentage signal change for most activated pixels, and that MTR increased with task activation (5).…”
mentioning
confidence: 99%
“…Spatially-selective ASL techniques with multiple labeling delays have been developed to estimate the arterial cerebral blood volume (29,30). Other approaches are to combine ASL with magnetization transfer effects (31,32) or to use the inflow-based Vascular-space-occupancy (VASO) MRI (33,34). A sophisticated T 2 * -based relaxation model has also been proposed for measuring venous cerebral blood volume (35).…”
Section: Introductionmentioning
confidence: 99%